Guided and motor imagery for pain management and functional recovery after arthroplasty of the hip or knee: A pragmatic prospective mixed-methods study - van Wietmarschen, Herman A.; Busch, Martine; Jong, Miek C. (Integrative medicine research, 2026)
Athroplastic surgery often results in acute post-operative pain, hindering rehabilitation compliance. To improve pain management and functional recovery, guided and motor imagery (GMI) exercises were introduced in hip and knee arthroplasty. A pragmatic prospective mixed-methods implementation evaluation was conducted at the orthopaedic department of Schakelring, the Netherlands. 80 subjects underwent a 4-week rehabilitation program including GMI after knee or hip arthroplasty. Outcomes included self-reported pain, Timed Up & Go test, 10-meter walk test, and medication use compared with a historical control group. A process evaluation was based on 6 meeting reports, a focus group and 8 interviews. Last measured pain scores were significantly lower in the GMI group compared to control (p = 0,030, Standard Mean Difference (SMD) = 0,87). Pain scores reduced over time in the GMI knee group compared to control (p = 0,015, SMD = 1,15), not in the hip group (p = 0,39, SMD = 0,43). Better Timed Up & Go and 10-meter walk test in GMI knee group versus control at the end of the 4 week rehabilitation period (p = 0,006 and p = 0,027). Thematic analysis of meetings, focus group and interviews resulted in the following critical themes for implementation were: individual adaptation, embedding in the rehabilitation program, motivation and attitudes of staff, perceived support, monitoring of outcome and creating a learning history, perceived effects. Monitoring and evaluating the implementation process and positive clinical results facilitated the implementation of GMI in the rehabilitation setting in the Netherlands.